A curated walk with peer researchers and their communities: Engaging a research journey toward meaningful impact - Bradley Rink; Gina Porter; Bulelani Maskiti; Sam Clark; Caroline Barber; Peer Researchers (Gateways)
As a collective of peer researchers, scholars and members of a non-profit organisation, we have come together to share a curated walk through low-income communities in Cape Town and London. We do so with the intent of exploring the embodied and social experiences of walking and writing research differently through a collaborative process of listening, co-creating and sharing knowledge about the pedestrian mobilities of young men as mediated by the precarities of urban life. Our walking-writing practices are a hybrid of the actual practices of walking and potential for enacting change by valuing the everyday experiences and knowledge of peer researchers. The curated walk that we share guides readers on the research journey that we have taken together from the homes of those involved to the metaphorical centre of power in the cities/regions where our work takes place, with the intention of long-term, meaningful impact.